2016
DOI: 10.1088/2053-1583/4/1/015028
|View full text |Cite
|
Sign up to set email alerts
|

Characterization methods dedicated to nanometer-thick hBN layers

Abstract: Abstract.Hexagonal boron nitride (hBN) regains interest as a strategic component in graphene engineering and in van der Waals heterostructures built with two dimensional materials. It is crucial then, to handle reliable characterization techniques capable to assess the quality of structural and electronic properties of the hBN material used. We present here characterization procedures based on optical spectroscopies, namely cathodoluminescence and Raman, with the additional support of structural analysis condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
80
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 80 publications
10
80
0
1
Order By: Relevance
“…(The value of Eg on quartz was found by us to be Eg ≈ 6.2 eV.) [5], energetically located inside the gap, and is termed, in bulk hBN, the D−series (D from diffuse) [31]. In addition to this, those authors identified two sharp peaks (S−series) in the region λ ∈ [210, 200] nm.…”
Section: Photoluminescence Of Hbn On Graphitementioning
confidence: 93%
“…(The value of Eg on quartz was found by us to be Eg ≈ 6.2 eV.) [5], energetically located inside the gap, and is termed, in bulk hBN, the D−series (D from diffuse) [31]. In addition to this, those authors identified two sharp peaks (S−series) in the region λ ∈ [210, 200] nm.…”
Section: Photoluminescence Of Hbn On Graphitementioning
confidence: 93%
“…The radiative recombination of free excitons dominates the CL spectra of both 10 BN and 11 BN exfoliated crystals with a maximum at 215 nm. The intensity of luminescence signals related to structural defects (227 nm) and deep defects (broadbands near 300 nm) remains much weaker than exciton signal (17.8 and 3.6 times lower for 10 BN and 11 BN), which indicates that the quality of APHT BN crystals is close to HPHT ones [41]. The control of the boron isotopes results in a slight energy shift for the series of narrow lines due to various phonon modes, including longitudinal and transverse optical (LO, TO) and longitudinal and transverse acoustic (LA, TA) phonons, which assist the indirect exciton recombination in BN, as seen in Fig.…”
mentioning
confidence: 90%
“…1(b) we can clearly distinguish the in-plane E 2g Raman mode of the two isotopes positioned at 1391.0 cm −1 and 1355.2 cm −1 for 10 BN and 11 BN respectively. The width of this peak is commonly used as a measure for the crystallinity of BN [41]. In the highest quality HPHT grown BN crystals with the natural distribution of boron the lowest width observed is 7.3 cm −1 [41], mainly broadened by isotopic disorder.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…h-BN films thickness was determined from their optical contrast (OC) using the cross-correlated calibration procedure with Atomic Force Microscopy measurements as detailed in [2,6]. This procedure insures a thickness uncertainty within ± 0.2L in the range of 1-20L range [6]. The…”
mentioning
confidence: 99%